Formulation of asphalt emulsions with lignin derivatives and its behavior with mixtures of stony materials - Pierini, Claudia; Bracho, Carlos; Gonzáles, Gioconda (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
Véase archivo PDF